Kontribusi Social Support Dalam Meningkatkan Work Engagement Pada Perempuan Bekerja Yang Menjalani Peran Ganda - Sulis Mariyanti; Lita Patricia Lunanta; Aisyah Ratnaningtyas (Departement of Mathematics Education, 2024)
Carrying out multiple roles for some working women is a tough, tiring and challenging role. On the one hand, as a mother you are required to be able to complete household tasks satisfactorily for yourself and your family. On the other hand, as an employee a mother is also required to be engaged in her work to show maximum performance. One of the factors that contributes to work engagement in women who play multiple roles is social support. The aim of this research is to determine the influence of social support on work engagement of working women who play multiple roles. This research method is a quantitative-causality type with a purposive sampling technique, involving 201 working and married mothers in Indonesia. The social support measuring tool refers to the theory of Sarafino & Smith (2011) with 35 valid items and reliability (α) = 0.915. The work engagement scale uses the Utrecht Employee Engagement Scale (UWES) from Schaufeli and Bakker (UWES) which was adapted from Titien (2016) with 28 valid items and reliability (α) = 0.922. The results of this research show that there is an influence of social support on work engagement in working women who play dual roles with a significant (p) value of 0.000 (p < 0.05), with a simple linear regression equation Y = 0.372 + 0.062. Social support give a quite large contribution of 54.4% to work engagement.